A method for catalytic conversion of polyurethane
Patent Information
- Application Number
- CN202410447567.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-15
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-04-15
AI Technical Summary
[0003]本申请的目的在于提供一种聚氨酯催化转化的方法,以高效利用聚氨酯塑料,解决聚氨酯降解的问题,并催化转化制备得到高值聚合物
[0009]本申请提供了一种聚氨酯催化转化的方法,提供两步串联的升级催化转化方法,将聚氨酯塑料通过“解聚-聚合”转化为高值聚合物,包括工程塑料(Engineering plastic)聚酰亚胺和生物可降解塑料(Biodegradable plastic)聚内酯,高效利用了聚氨酯塑料,解决了聚氨酯降解的问题,实现了聚氨酯塑料升级催化转化制备高值化学品。
Smart Images

Figure CN120829581B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of plastics processing technology, and in particular to a method for the catalytic conversion of polyurethane. Background Technology
[0002] Polyurethane (PU) plastics are widely used in numerous fields due to their excellent physicochemical properties. However, their good thermal stability, inherent cross-linked structure, and the complexity of their monomers present significant challenges in post-use degradation. Currently, pyrolysis, alcoholysis, aminolysis, and hydrogenolysis are some of the more commonly used degradation methods for polyurethane. However, pyrolysis often requires higher reaction temperatures and consumes more energy; alcoholysis and aminolysis offer relatively mild degradation conditions, but only one type of monomer can be recovered, limiting their wider application. Hydrogenolysis is an atom-economical degradation method with mild degradation conditions, yielding both amines and alcohols as basic chemicals. Even though some degradation methods for plastics have been developed, the further catalytic conversion of polyurethane to prepare higher-value chemicals or polymers remains a significant challenge. Summary of the Invention
[0003] The purpose of this application is to provide a method for the catalytic conversion of polyurethane, so as to efficiently utilize polyurethane plastics, solve the problem of polyurethane degradation, and catalytically convert it to prepare high-value polymers. The specific technical solution is as follows:
[0004] This application provides a method for the catalytic conversion of polyurethane, which includes depolymerization and polymerization;
[0005] The depolymerization process includes: taking polyurethane, adding a first catalyst and a first solvent, and heating to 180–210°C under hydrogenolysis reaction conditions to carry out a hydrogenolysis reaction to obtain monomers; the hydrogenolysis reaction conditions include introducing a hydrogenolysis atmosphere and / or adding methanol (MeOH); the hydrogenolysis atmosphere is selected from a hydrogen atmosphere or a mixed atmosphere of CO2 and hydrogen; the monomers include at least two of the following: primary diamine compounds, polyols, and lactones.
[0006] The aggregation includes:
[0007] The aromatic amine compound is dissolved in a second solvent, and an anhydride is added to carry out a first polymerization reaction to obtain polyimide (PI); and / or,
[0008] In an anhydrous and oxygen-free environment, the lactone compound is placed in a third solvent, and an initiator and a third catalyst are added. The second polymerization reaction is carried out at -40 to -20°C to obtain polylactone (PL).
[0009] This application provides a method for the catalytic conversion of polyurethane, which provides a two-step tandem upgraded catalytic conversion method to convert polyurethane plastics into high-value polymers, including engineering plastics such as polyimide and biodegradable plastics such as polylactone, through "depolymerization-polymerization". This method makes efficient use of polyurethane plastics, solves the problem of polyurethane degradation, and realizes the upgraded catalytic conversion of polyurethane plastics to prepare high-value chemicals.
[0010] Of course, implementing any product or method of this application does not necessarily require achieving all of the advantages described above at the same time. Attached Figure Description
[0011] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other embodiments can be obtained based on these drawings.
[0012] Figure 1 The product yields of aromatic diamine compounds, diol compounds, and lactone compounds in Examples 1-8 and Comparative Examples 1-2 are shown.
[0013] Figure 2 The degradation product yields of PU1 as a function of degradation time are shown in Examples 1 and 9-11;
[0014] Figure 3 The amount of methanol generated at different degradation times during the reactions of Examples 1 and 9-11 is shown;
[0015] Figure 4 The degradation product yields of PU2 as a function of degradation time are shown in Examples 2 and 12-14.
[0016] Figure 5 The figures show the amount of methanol generated at different degradation times during the reactions in Examples 2 and 12-14, as well as the amount of methanol generated at different degradation times without the addition of PU.
[0017] Figure 6 The results of PU2 degradation product yield as a function of degradation temperature are shown in Examples 2, 15-17;
[0018] Figure 7 The amounts of methanol generated at different degradation temperatures during the reactions in Examples 2, 15-17 are shown.
[0019] Figure 8 The results of the degradation product yield of PU2 in Examples 2 and 18-19 are shown as the CO2 / H2 molar ratio changes with the introduction of hydrogenolysis atmosphere.
[0020] Figure 9 The amounts of methanol produced during reactions 18-19 in Examples 2 are shown under different CO2 / H2 molar ratios.
[0021] Figure 10 Examples 20-23 show the yield results of degradation products of different polyurethane plastics;
[0022] Figure 11 The results of the cyclic stability of the catalyst of this application in the polyurethane catalytic degradation test are shown;
[0023] Figure 12 The results show the degradation product quality of the polyurethane tire in Example 24 as a function of degradation time.
[0024] Figure 13 The product yields of butanediol to butyrolactone produced in Example 25 at different reaction times are shown.
[0025] Figure 14 The infrared spectral detection results of the polyimide in this application are shown;
[0026] Figure 15 The energy storage density test results of the polyimide of this application used in high-temperature film capacitors are shown;
[0027] Figure 16 The tensile properties of the polylactone material obtained by polymerization in Example 28 are shown.
[0028] Figure 17 The results of proton NMR spectra of the polylactone, its monomers, and the monomers after recycling are shown. Detailed Implementation
[0029] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. All other embodiments obtained by those skilled in the art based on this application are within the scope of protection of this application.
[0030] This application provides a method for the catalytic conversion of polyurethane, which includes depolymerization and polymerization;
[0031] The depolymerization process includes: taking polyurethane, adding a first catalyst and a first solvent, and heating to 180–210°C under hydrogenolysis reaction conditions to carry out a hydrogenolysis reaction to obtain a monomer; the hydrogenolysis reaction conditions include introducing a hydrogenolysis atmosphere and / or adding methanol; the hydrogenolysis atmosphere is selected from a hydrogen atmosphere or a mixed atmosphere of CO2 and hydrogen; the monomer includes at least two of aromatic amine compounds, diol compounds, and lactone compounds.
[0032] The aggregation includes:
[0033] The aromatic amine compound is dissolved in a second solvent, and an acid anhydride is added to carry out a first polymerization reaction to obtain a polyimide; and / or,
[0034] In an anhydrous and oxygen-free environment, the lactone compound is placed in a third solvent, and an initiator and a third catalyst are added. A second polymerization reaction is carried out at -40 to -20°C to obtain polylactone.
[0035] This application provides a method for the catalytic transformation and upgrading of polyurethane plastics through degradation. It achieves a highly efficient process of degrading polyurethane plastics into basic chemical monomers via catalytic hydrogenolysis. Furthermore, the separated aromatic amine compounds and lactone compounds are used for polymerization to obtain at least two high-value polymers: polyimide and polylactone. This method efficiently utilizes polyurethane plastics, solves the problem of polyurethane degradation, and realizes the upgraded catalytic transformation of polyurethane plastics to prepare high-value chemicals. In this application, the aromatic amine compounds include aromatic diamine compounds.
[0036] In some embodiments, the hydrogenolysis reaction conditions include a mixed atmosphere of CO2 and hydrogen, or a hydrogen atmosphere with the addition of methanol. The inventors have found that when a mixed atmosphere of CO2 and hydrogen, or a hydrogen atmosphere with the addition of methanol is used, the yield of polyurethane hydrogenolysis products is higher, and the catalytic degradation effect is further improved.
[0037] In some embodiments, the hydrogenolysis reaction temperature is 190-210°C, and the hydrogenolysis reaction time is 1-30 hours; preferably, the hydrogenolysis reaction temperature is 195-205°C. This application shows good catalytic degradation of polyurethane at a hydrogenolysis reaction temperature of 190-210°C; and even better catalytic degradation at a hydrogenolysis reaction temperature of 195-205°C. In this application, controlling the hydrogenolysis reaction time within 1-30 hours achieves a good catalytic degradation effect on polyurethane.
[0038] In some embodiments, the hydrogen atmosphere has a pressure of 1.5-3 MPa; the mixed atmosphere of CO2 and hydrogen has a molar ratio of CO2 to hydrogen of 1:(1-3) and a pressure of 2.5-4 MPa. In this application, adjusting the pressure of the introduced hydrogen decomposition atmosphere within the range of this application can enable polyurethane to achieve a better catalytic degradation effect.
[0039] In some embodiments, the hydrogenolysis reaction conditions include a polyurethane mass to methanol molar ratio of (50-200) mg:1 mmol when methanol is added. By controlling the polyurethane mass and methanol molarity within the above range, the yield of the polyurethane hydrogenolysis depolymerization product is higher, and the catalytic degradation effect is better.
[0040] In some embodiments, the hydrogen atmosphere has a pressure of 1.5-3 MPa; the mixed atmosphere of CO2 and hydrogen has a molar ratio of CO2 to hydrogen of 1:(1-3) and a pressure of 2.5-4 MPa.
[0041] The hydrogenolysis reaction conditions include, when methanol is added, a mass ratio of the polyurethane to the methanol of (50-200) mg: 1 mmol.
[0042] In some embodiments, the first polymerization reaction includes the following steps: stirring at room temperature (rt) for 4-8 hours, then maintaining under a nitrogen atmosphere for 20-50 minutes, then heating to 80-120°C and maintaining for 1-3 hours, then heating to 140-160°C, 180-220°C, 240-260°C, and 280-320°C respectively and maintaining for 1-2 hours each, cooling to room temperature, separating, and drying. Using the first polymerization reaction of this application, polyimide with excellent energy storage performance can be obtained. In this application, "room temperature" is 25±5°C.
[0043] This application does not have any particular limitation on the acid anhydride, as long as it can achieve the purpose of this application; in some embodiments, the acid anhydride is selected from at least one of pyromellitic dianhydride and 4,4'-(hexafluoroisopropyl)-phthalic anhydride.
[0044] In this application, there is no particular limitation on the time of the second polymerization reaction, as long as the purpose of this application can be achieved. In some embodiments, the time of the second polymerization reaction is 4-8 hours.
[0045] In some embodiments, the first catalyst is selected from at least one of ZnO-ZrO2 / Cu and ZrO2 / Cu, and the first solvent is selected from at least one of tetrahydrofuran and 1,4-dioxane; and / or,
[0046] The second solvent is selected from N-methylpyrrolidone (NMP), and the anhydride is selected from at least one of pyromellitic dianhydride and 4,4'-(hexafluoroisopropyl)-phthalic anhydride; and / or,
[0047] The third solvent is selected from at least one of tetrahydrofuran (THF), 1,4-dioxane, and chloroform; the initiator is selected from benzyl alcohol (BnOH); and the third catalyst is selected from a yttrium compound complexed with a tetradentate aminoalkoxybisphenolic acid ligand. Specifically, it may include: YN compounds: Using the reagents described in this application, efficient catalytic degradation of polyurethane and its upgraded catalytic conversion into polyimide and / or polylactone can be achieved, thus realizing the efficient utilization and conversion of polyurethane.
[0048] In some embodiments, the mass ratio of the polyurethane to the volume ratio of the first solvent is (5-100) mg:1 mL, and the mass ratio of the polyurethane to the first catalyst is (1-10):1; and / or,
[0049] The molar ratio of the aromatic amine compound to the acid anhydride is 1:(0.5-2), and the mass ratio of the aromatic amine compound to the volume ratio of the second solvent is (0.1-2) g:2 mL; and / or,
[0050] The ratio of the mass of the lactone compound, the mass of the initiator, the mass of the third catalyst, and the volume of the third solvent is (1-2) g : (0.05-0.2) g : (0.05-0.2) g : 2 mL. By adjusting the material ratio within the above range, the polyurethane of this application can exhibit better catalytic degradation effects and achieve more complete conversion to synthesize polyimide and / or polylactone, resulting in materials with excellent properties.
[0051] In some embodiments, the lactone compound further includes a lactone compound prepared by catalytic dehydrogenation of the diol compound; the preparation step of catalytic dehydrogenation of the diol compound includes:
[0052] The diol compound is reacted with a fourth catalyst and a fourth solvent at 0.8-1.5 MPa and an inert atmosphere at 200-250°C to obtain a lactone compound; the inert atmosphere is selected from at least one of nitrogen and argon. This application does not have a particular limitation on the reaction time, as long as the objective of this application can be achieved. In some embodiments, the catalytic dehydrogenation reaction time is 8-15 hours.
[0053] In some embodiments, the fourth catalyst is selected from at least one of ZnO-ZrO2 / Cu and ZrO2 / Cu; the fourth solvent is selected from at least one of tetrahydrofuran and 1,4-dioxane. By employing the above reagents, this application can achieve high yields of lactone compounds.
[0054] In some embodiments, the mass ratio of the diol compound to the fourth catalyst is (3-6):1; the mass ratio of the diol compound to the volume ratio of the fourth solvent is (20-40) mg:1 mL. By adjusting the material ratio within the above range, the catalytic activity of the fourth catalyst can be improved, the conversion rate of the diol compound can be increased, and the yield of the lactone compound can be increased.
[0055] For example, in the polyurethane catalytic conversion method of this application, the reaction formulas are shown below. The monomers in the figures are specific examples of various compounds and are not intended to limit this application.
[0056]
[0057] Example
[0058] The embodiments and comparative examples provided below illustrate the implementation of this application in more detail. Various tests and evaluations were performed according to the methods described below. Unless otherwise specified, "parts" and "%" are quality bases. In this application, "overnight" refers to 12 ± 6 hours.
[0059] Catalyst preparation
[0060] 10 mmol Cu(NO3)2·3H2O, 2.5 mmol Zr(NO3)4·5H2O, and 1.25 mmol Zn(NO3)2·6H2O were dissolved in 100 mL of ethanol to obtain a mixture. An ethanol solution containing 0.5 M (mol / L) oxalic acid was added dropwise to the mixture for co-precipitation, accompanied by strong magnetic stirring at 600 rpm. After the addition was complete, the turbid liquid was centrifuged to obtain a precipitated solid, which was dried overnight in a 60 °C oven to obtain a blue solid. This solid was ground into powder in a mortar and then calcined in air in a muffle furnace at 400 °C for 2 h to obtain the catalyst ZnO-ZrO2 / Cu. Before each use, the calcined catalyst was activated in an atmosphere of 10 vol% H2 / 90 vol% Ar at 230 °C for 2 h. The activated catalyst was then transferred to a reaction vessel for further reaction.
[0061] Test methods and equipment:
[0062] Quantitative analysis methods for aromatic amine compounds, glycol compounds, lactone compounds, and methanol:
[0063] Quantitative analysis was performed using a gas chromatograph (GC) with an Agilent 7820A instrument.
[0064] Infrared detection of polyimide:
[0065] The Bruker Alpha instrument was used to test the polyimide, and the infrared spectrum of the polyimide was obtained.
[0066] Energy storage density test:
[0067] A high-temperature thin-film capacitor was obtained by placing Cu electrodes with a diameter of 3.4 mm and a thickness of 50 nm at both ends of a polyimide film. The dielectric constant and dielectric loss of the polyimide film were tested using an Agilent LCR (4294A) instrument, and the energy storage density of the high-temperature thin-film capacitor was tested under a high-voltage amplification system at 150 °C.
[0068] Tensile property test:
[0069] The tensile stress and strain of polylactone shaped like a bone were tested using an INSTRON 3365 (50N load cell) test system, with a test value of 5 mm min. -1 The strain rate of the tension.
[0070] Monomer recycling performance test:
[0071] Polylactone and catalyst Y(CH2SiMe3)3(THF)2 were placed in a 10 mL Schlenk tube, and catalytic degradation was carried out at 250 °C under a nitrogen atmosphere. The reaction was then carried out via... 1 ¹H-NMR is used for quantitative analysis of monomers.
[0072] Depolymerization Example
[0073] Example 1
[0074] 200 mg of PU1 (synthesized from xylene diisocyanate and triethylene glycol, with a weight-average molecular weight Mw of 500,000), 200 mg of ZnO-ZrO2 / Cu, and 30 mL of THF were added to a reaction vessel. A mixed atmosphere of CO2 and hydrogen was introduced, with a CO2 / H2 ratio of 1 mol / 3 mol and a pressure of 3 MPa. The mixture was heated to 200 °C for hydrogenolysis for 4 h to obtain the product monomers, including aromatic diamines: 4,4'-diaminodiphenylmethane, N-methyl-4,4'-methyldiphenylamine, and 4,4'-methylenebis(N-methylaniline), and diols: triethylene glycol. The reaction process was qualitatively and quantitatively analyzed by gas chromatography, and the product yield was 89%.
[0075] The formula for calculating the yield is:
[0076] Example 2-24
[0077] Except for adjusting the corresponding preparation parameters as shown in Table 1, the rest is the same as in Example 1. The monomers obtained in Example 2 include: aromatic diamine compounds: 4,4'-diaminodiphenylmethane, N-methyl-4,4'-methyldiphenylamine, 4,4'-methylenebis(N-methylaniline); diol compounds: butanediol (BDO), dipropylene glycol (DPG); and lactone compounds: butyrolactone (BL), caprolactone (CL).
[0078] Comparative Examples 1-2
[0079] Except for adjusting the corresponding preparation parameters as shown in Table 1, everything else is the same as in Example 1.
[0080] Table 1
[0081]
[0082]
[0083]
[0084] Note: " / " in the table indicates that there are no corresponding preparation parameters.
[0085] The product yields of aromatic diamines, diols, and lactones in Examples 1-8 and Comparative Examples 1-2 are as follows: Figure 1 As shown, according to Table 1 and Figure 1 Analysis revealed that PU1 and PU2 underwent more complete degradation in the presence of a catalyst and a CO2 / H2 reaction atmosphere, as shown in Examples 1-2. The yields of aromatic diamines, diols, and lactones reached 89% and 82%, respectively, significantly higher than the degradation effects under hydrogen or methanol-only reaction conditions in Examples 3-6. These results further illustrate the importance of introducing CO2 during hydrogenolysis. CO2 can be reduced by H2 to produce methanol, which promotes the degradation rate of PU. The introduction of both H2 and methanol, as seen in Examples 7-8, resulted in degradation effects similar to those in Examples 1-2, further demonstrating that CO2, by producing methanol during catalytic hydrogenolysis, enhances the catalytic degradation efficiency of polyurethane. Comparison with reaction conditions without a catalyst, such as Comparative Examples 1-2, revealed that polyurethane hardly depolymerized under these conditions, with only a small amount of lactones produced, further indicating that the catalytic hydrogenolysis of polyurethane occurs on the catalyst surface.
[0086] The yield results of degradation products of PU1 as a function of degradation time in Examples 1 and 9-11 are as follows: Figure 2As shown, the amount of methanol generated at different degradation times during the reaction was measured, and the results are as follows. Figure 3 As shown; the yield results of degradation products of PU2 as a function of degradation time in Examples 2 and 12-14 are as follows. Figure 4 As shown, the amount of methanol generated at different degradation times during the reaction was measured, and the amount of methanol generated at different degradation times without the addition of PU was also measured. The results are as follows. Figure 5 As shown. Figure 3 and Figure 5 The results further demonstrate that introducing CO2 during hydrogenolysis, which can be reduced by H2 to produce methanol, is beneficial for promoting the degradation rate of PU. According to Examples 1-2 and Examples 9-14, it can be observed that both PU1 and PU2 exhibit good degradation effects within 1-4 hours, and the yield of degradation products increases accordingly with time.
[0087] The yield results of PU2 degradation products as a function of degradation temperature in Examples 2, 15-17 are as follows: Figure 6 As shown, the amount of methanol generated during the reaction at different degradation temperatures was measured, and the results are as follows. Figure 7 As shown, the results indicate that PU degradation can be achieved at temperatures ranging from 180 to 210℃, with better catalytic degradation at temperatures ranging from 190 to 210℃.
[0088] The yield results of degradation products of PU2 in Examples 2, 18-19 as a function of the CO2 / H2 molar ratio in the hydrogenolysis atmosphere are as follows: Figure 8 As shown, the amount of methanol produced during the reaction was measured under different CO2 / H2 molar ratios, and the results are as follows. Figure 9 As shown, the results indicate that PU degradation can be achieved under conditions where the CO2 / H2 molar ratio is 1:1-3, and the catalytic degradation efficiency is better when the CO2 / H2 molar ratio is 1:2-3.
[0089] Catalytic degradation experiments were conducted on common polyurethane plastics found in daily life. Waste polyurethane plastics could include polyurethane shoe soles, plastic pipes, tires, and traffic safety rods, as shown in Examples 20-23. The yield results of degradation products for different polyurethane plastics in Examples 20-23 are as follows: Figure 10 As shown, analysis of the reaction products revealed that different polyurethane waste plastics all exhibited good degradation product yields, with polyurethane tires showing the best degradation effect. Using polyurethane tires as a substrate, the cyclic stability of the catalyst in this application was tested. Specifically, as shown in Example 22, a catalytic degradation experiment was conducted on polyurethane tires. After each reaction, the catalyst was separated by centrifugation, reactivated, and then the polyurethane tire catalytic degradation experiment was repeated. The product quality results after six cycles of stability testing are as follows: Figure 11As shown in the results, the degradation activity of the catalyst was not affected, indicating that the catalyst of this application has good stability.
[0090] A scale-up experiment was conducted using polyurethane tires as a substrate, as shown in Example 24. After 30 hours of reaction, the mixture solution was collected and purified by organic gel electrophoresis to obtain monomeric aromatic diamine compounds, including 0.9 g of an aromatic primary amine: 4,4'-diaminodiphenylmethane and 0.7 g of a monosubstituted methyl aromatic amino compound: N-methyl-4,4'-methyldiphenylamine, 0.95 g of a diol compound: butanediol, and 0.45 g of a lactone compound: including butyrolactone / caprolactone = 3 mmol / 1 mmol. The degradation product mass results of the polyurethane tires in Example 24 as a function of degradation time are shown below. Figure 12 As shown, polyurethane achieved a good catalytic degradation effect after 30 hours of degradation reaction.
[0091] Example 25
[0092] The monomer butylene glycol obtained in Example 24 was used to prepare butyrolactone by catalytic dehydrogenation. Specifically, 0.95 g of butylene glycol was added to 200 mg of ZnO-ZrO2 / Cu and 30 mL of THF under a nitrogen atmosphere of 1 MPa, and the reaction was carried out at 220 °C for 12 h to obtain 8 mmol of butyrolactone. The obtained butyrolactone was combined with the lactone compounds purified by the degradation and separation of polyurethane plastics in Example 24 to obtain 1.3 g of lactone compounds, including butyrolactone / caprolactone = 11 mmol / 1 mmol. The product yields of butyrolactone from butylene glycol at different reaction times are shown below. Figure 13 As shown, this application further realizes the efficient utilization of polyurethane plastic degradation products.
[0093] Aggregate Examples
[0094] Example 26
[0095] 0.9 g of the aromatic diamine compound (Diamine) obtained in Example 24 was dissolved in 5 mL of NMP, and an equimolar amount of acid anhydride, pyromellitic dianhydride, was added. The mixture was stirred at room temperature for 6 h. The solution was then dropped onto a clean glass plate and kept under a nitrogen atmosphere for 30 min. It was then heated to 100 °C and held for 2 h to remove the solvent, followed by heating to 150 °C, 200 °C, 250 °C, and 300 °C, each held for 1 h. The mixture was then cooled to room temperature, and the resulting polyimide film was placed in deionized water. The polyimide film was scraped off the glass plate and then kept in a vacuum oven at 100 °C for 12 h. The resulting polyimide PI1 film had a thickness of 10-12 μm.
[0096] Example 27
[0097] Except for replacing the acid anhydride, pyromellitic dianhydride, with 4,4'-(hexafluoroisopropyl)-diphthalic anhydride, the rest was the same as in Example 26, and a polyimide PI2 film with a thickness of 10-12 μm was obtained.
[0098] The reaction formulas for preparing polyimides by polymerizing aromatic diamine compounds with acid anhydrides are shown below, where Thermal imidization refers to thermal imidization:
[0099]
[0100] Infrared spectroscopy was performed on polyimide films PI1 and PI2, and the infrared spectra of the polyimide films are shown below. Figure 14 As shown, and compared with commercial Kapton polyimide film (manufactured by DuPont), the energy density of each high-temperature film capacitor was tested. The energy density test results of each high-temperature film capacitor are as follows. Figure 15 As shown, the polyimide material synthesized in this application exhibits superior performance when used as a high-temperature thin-film capacitor, with a storage density reaching up to 6.0 J / cm². 3 .
[0101] Example 28
[0102] In a glove box (water content <0.01ppm, oxygen content <0.01ppm), 1.3g of the lactone compound obtained in Example 25 was dissolved in 2mL of tetrahydrofuran solution, and 0.1g of BnOH initiator and 0.1g of catalyst (cat) were added. The polymerization reaction was carried out at -30°C for 6h to obtain polylactone (P(BL-co-CL)), and the reaction formula is as follows:
[0103]
[0104] The degree of polymerization of the polylactone was characterized by nuclear magnetic resonance (NMR), yielding a polylactone with a number-average molecular weight (Mn) of 56.3 kgmol / L. -1 ).
[0105] The lactone compounds obtained from the degradation of polyurethane were used to synthesize polylactone polymers, and the tensile mechanical properties of the synthesized polylactone materials were tested. The tensile property test results of the polylactone material obtained in Example 28 are as follows: Figure 16 As shown, the polylactone material synthesized in this application exhibits tensile properties that are at least 10 times longer than its own length.
[0106] The monomer recycling performance of the synthesized polylactone material was tested and analyzed by NMR. Figure 17As shown, the lactone monomers can be completely recovered through catalysis. This indicates that the polylactone material prepared in this application can be recycled and reused.
[0107] In summary, this application uses waste polyurethane materials as raw materials and achieves the upgrading and transformation of polyurethane plastics through a two-step catalytic tandem "depolymerization-polymerization" process, converting them into at least two high-value polymers: polyimide and polylactone.
[0108] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.
[0109] The various embodiments in this specification are described in a related manner. The same or similar parts between the various embodiments can be referred to each other. Each embodiment focuses on describing the differences from other embodiments.
[0110] The above description is only a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the scope of protection of this application.
Claims
1. A method for the catalytic conversion of polyurethane, comprising depolymerization and polymerization; The depolymerization includes: Polyurethane is taken, a first catalyst and a first solvent are added, and the mixture is heated to 180-210°C under hydrogenolysis reaction conditions to carry out a hydrogenolysis reaction to obtain a monomer; the hydrogenolysis reaction conditions include the introduction of a hydrogenolysis atmosphere and / or the addition of methanol; the hydrogenolysis atmosphere is selected from a hydrogen atmosphere or a mixed atmosphere of CO2 and hydrogen; the monomer includes at least two of aromatic amine compounds, diol compounds, and lactone compounds; the first catalyst is selected from at least one of ZnO-ZrO2 / Cu and ZrO2 / Cu. The aggregation includes: The aromatic amine compound is dissolved in a second solvent, and an acid anhydride is added to carry out a first polymerization reaction to obtain a polyimide; and / or, In an anhydrous and oxygen-free environment, the lactone compound is placed in a third solvent, and an initiator and a third catalyst are added. A second polymerization reaction is carried out at -40 to -20°C to obtain polylactone.
2. The method according to claim 1, wherein, The hydrogenolysis reaction conditions include introducing a mixed atmosphere of CO2 and hydrogen, or introducing a hydrogen atmosphere and adding methanol.
3. The method according to claim 1, wherein, The hydrogenolysis reaction is carried out at a temperature of 190-210℃ for 1-30 hours.
4. The method according to claim 1, wherein, The hydrogen atmosphere has a pressure of 1.5-3 MPa; the mixed atmosphere of CO2 and hydrogen has a molar ratio of CO2 to hydrogen of 1:(1-3) and a pressure of 2.5-4 MPa. The hydrogenolysis reaction conditions include, when methanol is added, the mass ratio of the polyurethane to the methanol is (50-200) mg: 1 mmol.
5. The method according to claim 1, wherein, The steps of the first polymerization reaction include: stirring at room temperature for 4-8 hours, then maintaining under a nitrogen atmosphere for 20-50 minutes, then heating to 80-120°C and maintaining for 1-3 hours, then heating to 140-160°C, 180-220°C, 240-260°C, and 280-320°C respectively and maintaining for 1-2 hours, cooling to room temperature, separating, and drying.
6. The method according to claim 1, wherein, The first solvent is selected from at least one of tetrahydrofuran and 1,4-dioxane; and / or, The second solvent is selected from N-methylpyrrolidone, and the anhydride is selected from at least one of pyromellitic dianhydride and 4,4'-(hexafluoroisopropyl)-phthalic anhydride; and / or, The third solvent is selected from at least one of tetrahydrofuran, 1,4-dioxane, and chloroform; the initiator is selected from benzyl alcohol; and the third catalyst is selected from: 。 7. The method according to claim 1, wherein, The mass ratio of the polyurethane to the volume ratio of the first solvent is (5-100) mg:1 mL, and the mass ratio of the polyurethane to the first catalyst is (1-10):1; and / or, The molar ratio of the aromatic amine compound to the acid anhydride is 1:(0.5-2), and the mass ratio of the aromatic amine compound to the volume ratio of the second solvent is (0.1-2) g: 2 mL; and / or, The ratio of the mass of the lactone compound, the mass of the initiator, the mass of the third catalyst, and the volume of the third solvent is (1-2) g : (0.05-0.2) g : (0.05-0.2) g : 2 mL.
8. The method according to claim 1, wherein, The lactone compound further includes a lactone compound prepared by catalytic dehydrogenation of the diol compound; the preparation step of catalytic dehydrogenation of the diol compound includes: The diol compound is reacted with a fourth catalyst and a fourth solvent at 0.8-1.5 MPa and an inert atmosphere at 200-250 °C to obtain a lactone compound; the inert atmosphere is selected from at least one of nitrogen and argon.
9. The method according to claim 8, wherein, The fourth catalyst is selected from at least one of ZnO-ZrO2 / Cu and ZrO2 / Cu; the fourth solvent is selected from at least one of tetrahydrofuran and 1,4-dioxane.
10. The method according to claim 8, wherein, The mass ratio of the diol compound to the fourth catalyst is (3-6):1; the mass ratio of the diol compound to the volume ratio of the fourth solvent is (20-40) mg:1 mL.